Powołanie się przez podatnika przed organem podatkowym na fakt dokonania czynności cywilnoprawnej albo nieodpłatnego nabycia prawa majątkowego - Ostojski, Przemysław (Kwartalnik Prawa Podatkowego, 2015)
The content of the article deals with the issues concerning the conditions for applying penal rate of tax on civil law transactions and the tax on inheritance and donations, due to the failure to demonstrate the events of taxable and non-payment of due tax. The action which gives the tax authority the right to enitelment the sancion rate is the taxpeyer plead to the fact of the civil law transaction or gratuitous acquisition of property rights. The analysis must come to the conclusion that the plead of the taxpayer in the course of any tax proceeding or audit, tax audit or verification activities – the fact the civil law transaction or gratuitous acquisition of property law, should result in tax assessment by high – 20% rate, unless the taxpayer has not shown chargeable event and has not paid the tax due. Moreover “the reference to” in the meaning given to that expression by art. 3. 1 point 4 the tax on civil law transactions act and art. 6 point 4 tax on the inheritance and donations act, does not have to a special, separate the qualified taxpayer’s activity.